2013
DOI: 10.3109/10409238.2013.771132
|View full text |Cite
|
Sign up to set email alerts
|

Poly(A)-specific ribonuclease (PARN): An allosterically regulated, processive and mRNA cap-interacting deadenylase

Abstract: Deadenylation of eukaryotic mRNA is a mechanism critical for mRNA function by influencing mRNA turnover and efficiency of protein synthesis. Here, we review poly(A)-specific ribonuclease (PARN), which is one of the biochemically best characterized deadenylases. PARN is unique among the currently known eukaryotic poly(A) degrading nucleases, being the only deadenylase that has the capacity to directly interact during poly(A) hydrolysis with both the m(7)G-cap structure and the poly(A) tail of the mRNA. In short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 152 publications
1
85
0
6
Order By: Relevance
“…PARN is highly conserved in higher eukaryotes, but is not identified in yeast and fly [2,4,5]. Previous functional studies have shown that PARN is involved in several crucial physiological processes such as the meiotic maturation of frog oocytes [49], embryogenesis and stress response in plants [50,51] and stage-specific protein production in Trypanosoma brucei [52].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…PARN is highly conserved in higher eukaryotes, but is not identified in yeast and fly [2,4,5]. Previous functional studies have shown that PARN is involved in several crucial physiological processes such as the meiotic maturation of frog oocytes [49], embryogenesis and stress response in plants [50,51] and stage-specific protein production in Trypanosoma brucei [52].…”
Section: Discussionmentioning
confidence: 97%
“…Meanwhile, the depletion of Ccr4b/CNOT6L in NIH 3T3 cells increases the mRNA stability of p27 but not p21 [26]. Among the various deadenylases, PARN is unique due to its highly processive deadenylation activity in a cap-dependent manner (reviewed in [5]). PARN has been shown to participate in rapid deadenylation mediated by ARE [27], which has been shown to be a stabilizing element in the p21 mRNA.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In human and murine liver cells, 3′ adenylation mediated by the nucleotidyl transferase PAPD4 has been shown to stabilize miR-122 (19). In contrast, PAPD5 was recently found to aid in the maturation of SNORA63 and other small nucleolar RNAs in a pathway where oligoadenylation by PAPD5 is followed by 3′-to-5′ trimming by the exonuclease PARN (38,39) (Fig. S6).…”
Section: Significancementioning
confidence: 99%
“…65 This was attributed to the decreased phosphorylation of 4EBP, which allows dephosphorylated 4EBP to disrupt the eIF4E-eIF4G interaction that binds the cap much more strongly than eIF4E alone (nanomolar range compared with low micromolar range). 65,89,99 PARN interacts with FXR1a-microRNP in G0 and in immature oocytes, indicating a role in microRNA-mediated translation activation (Fig. 1).…”
Section: Parn Is Essential For Fxr1a-micrornp Mediated Translation Asmentioning
confidence: 99%